Sensory Characteristics of Black Currant Wines - Metz, Tapio (My University, 2023)
Fruit wines are fermented alcoholic beverages made from the juice of non-grape fruits, such as black currants, which are one of the largest berry crops in Finland. Fruit wines have a lot of market potential, especially in regions where viticulture does not thrive. In recent years, interest in the so-called non-Saccharomyces yeasts has been increasing and they have been reported to have positive effects on the sensory characteristics of wines as well as being potentially useful for producing wines with reduced alcohol content. The goal of this study was to determine the sensory-chemical differences between alcoholic black currant beverages fermented with Saccharomyces and non-Saccharomyces yeasts. The beverage samples (n=5) were fermented using different strains of Saccharomyces, Metschnikowia and Torulaspora yeasts. The sensory evaluation was performed by a trained panel (n=11), using a generic descriptive method. Twelve different attributes were analysed, which consisted of five odour attributes, six taste attributes and one texture attribute. The finished beverages had a strong black currant odour with a very sour and astringent taste. Three attributes had statistically significant differences in the samples: stuffy/musty odour, black currant odour and viscosity. Saccharomyces bayanus sample had a stronger stuffy odour compared to the others, as well as the most viscous mouthfeel. Torulaspora delbrueckii sample was the least viscous but had the strongest black currant odour. The sourness of black currants was enhanced further by the fermentation process, making it difficult for the panelists to distinguish other taste attributes. Generally, all the non-Saccharomyces yeast beverages had stronger black currant odour and weaker stuffy/musty odour, demonstrating their potential for improving the sensory qualities of alcoholic beverages.
Keywords: sensory analysis, black currant, fruit wine, non-Saccharomyces yeast